Secondary Prevention in Radiologically Isolated Syndromes and Prodromal Stages of Multiple Sclerosis - Amato, Maria Pia; De Stefano, Nicola; Inglese, Matilde; Morena, Emanuele; Ristori, Giovanni; Salvetti, Marco; Trojano, Maria (Frontiers in Neurology, 2022)
Following the extraordinary progress in the treatment of multiple sclerosis (MS), two major unmet needs remain: understanding the etiology of the disease and, hence, designing definitive cures (this perspective is neither at hand, nor it can be taken for granted that the etiologic targets will be readily treatable); the prevention of an overt and disabling disease, which seems to be a more realistic and pragmatic perspective, as the integration of genetic data with endophenotypes, MRI, and other biomarkers ameliorates our ability to identify early neuroinflammation. Radiologically isolated syndrome (RIS; diagnosed when the unanticipated MRI finding of brain spatial dissemination of focal white matter lesions highly suggestive of MS occurs in subjects without symptoms of MS, and with normal neurological examinations) and the recently focused “prodromal MS” are conditions at risk of conversion toward overt disease. Here, we explore the possibility of secondary prevention approaches in these early stages of neuroinflammation. RIS and prodromal MS are rare conditions, which suggest the importance of Study Groups and Disease Registry to implement informative clinical trials. We summarize ongoing preventive approaches in the early stages of the demyelinating process, especially in RIS conditions. Moreover, we highlight the importance of the biomarkers and the predictors of evolution to overt disease, which may be useful to select the individuals at risk of conversion to clinically isolated syndrome (CIS) and/or clinically definite MS. Finally, we illustrate the importance of the endophenotypes to test the frontline immunomodulatory approach for preventive strategies. Future investigations, especially in relatives of patients, based on MRI techniques and biological studies (better with integrated approaches) may provide opportunities to understand the MS early causal cascade and may help to identify a “therapeutic window” to potentially reverse early disease processes.